Nipple Pain in Breastfeeding Mothers: Incidence, Causes and Treatments - Jacqueline C. Kent (International Journal of Environmental Research and Public Health, 2015)
Background: Persistent nipple pain is one of the most common reasons given by mothers for ceasing exclusive breastfeeding. We aimed to determine the frequency of nipple pain as a reason for consultation, the most common attributed aetiologies, and the effectiveness of the advice and treatment given. Methods: All consultations at the Breast Feeding Centre of Western Australia (WA) were audited over two six-month periods in 2011 (n = 469) and 2014 (n = 708). Attributed cause(s) of nipple pain, microbiology results, treatment(s) advised, and resolution of pain were recorded. Results: Nipple pain was one of the reasons for consultation in 36% of cases. The most common attributed cause of nipple pain was incorrect positioning and attachment, followed by tongue tie, infection, palatal anomaly, flat or inverted nipples, mastitis, and vasospasm. Advice included correction of positioning and attachment, use of a nipple shield, resting the nipples and expressing breastmilk, frenotomy, oral antibiotics, topical treatments, and cold or warm compresses. Pain was resolving or resolved in 57% of cases after 18 days (range 2–110). Conclusion: The multiple attributed causes of nipple pain, possibly as a result of a cascade of events, suggests that effective early lactation management for prevention of nipple pain and early diagnosis and effective treatment are crucial to avoid early weaning.